2022
DOI: 10.1155/2022/7539520
|View full text |Cite|
|
Sign up to set email alerts
|

Significance of Cardiometabolic Index in Predicting Acute Exacerbation of Stable Chronic Obstructive Pulmonary Disease for Clinical Nursing

Abstract: Objective. To evaluate the level of cardiometabolic index (CMI) to predict the risk of acute exacerbation in patients with stable chronic obstructive pulmonary disease (COPD), and to provide a basis for early identification and intervention of high-risk patients in clinical nursing work. Methods. Patients with stable chronic obstructive pulmonary disease who were admitted to the outpatient department of respiratory medicine in a tertiary hospital or followed up after discharge from January to December 2021 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Sesak dan batuk masih menjadi masalah yang dikeluhkan oleh pasien dan keluarga di rumah maupun di saat pasien di rawat di RS. Hal ini dikaitkan dengan obstruksi progresif pada saluran nafas (Luo et al, 2022).…”
Section: Evaluasi Hasilunclassified
“…Sesak dan batuk masih menjadi masalah yang dikeluhkan oleh pasien dan keluarga di rumah maupun di saat pasien di rawat di RS. Hal ini dikaitkan dengan obstruksi progresif pada saluran nafas (Luo et al, 2022).…”
Section: Evaluasi Hasilunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%